NF-κB-mediated degradation of the coactivator RIP140 regulates inflammatory responses and contributes to endotoxin tolerance. - Ho, P; Tsui, Y; Feng, X; Greaves, D; Wei, L (2012)
Tolerance to endotoxins that is triggered by prior exposure to Toll-like receptor (TLR) ligands provides a mechanism with which to dampen inflammatory cytokines. The receptor-interacting protein RIP140 interacts with the transcription factor NF-κB to regulate the expression of genes encoding proinflammatory cytokines. Here we found lipopolysaccharide stimulation of kinase Syk-mediated tyrosine phosphorylation of RIP140 and interaction of the NF-κB subunit RelA with RIP140. These events resulted in more recruitment of the E3 ligase SCF to tyrosine-phosphorylated RIP140, which degraded RIP140 to inactivate genes encoding inflammatory cytokines. Macrophages expressing nondegradable RIP140 were resistant to the establishment of endotoxin tolerance for specific 'tolerizable' genes. Our results identify RelA as an adaptor with which SCF fine tunes NF-κB target genes by targeting the coactivator RIP140 and show an unexpected role for RIP140 degradation in resolving inflammation and endotoxin tolerance.